31.D. Workshop: Sustainable public health: better individual and professional choices. (30th September 2020) - ,; ,
Abstract: The Sustainable Development Goals (SDGs) call for urgent action and global partnership in order to solve the worlds' most complex problems, arguing that we cannot have good health and wellbeing or reduce inequalities without solving the consequences that come with climate change, the necessity of need for quality education and the importance of responsible consumption and production. The public health (PH) arena touches all of these problems. According to the 10 Essential Public Health Operations (EPHO) defined by the World Health Organization (WHO), PH services are meant to deliver health protection, health promotion and disease prevention to populations. In order to do that, these EPHO, and particularly EPHO3, include climate change, green health services and sustainable development as important issues to take into account when identifying current and future weaknesses in health services and PH interventions, and inform the development of new policies, programs or projects to address them. This workshop aims to provide useful insight on the current climate change situation and its impact on the populations' health across the globe; the importance of the contribution of PH in the creation of green health services; what we can do on an individual level to contribute to the achievement of the SDG; and how PH policies, programs and projects can contribute to EPHO3 and the achievement of better and sustainable population health states. This workshop provides up-to-date knowledge on what is happening in the world regarding sustainability, green health services and climate change's health impacts, which practical measures every PH professional can implement in their daily lives to improve their individual carbon footprint and contribute to the achievement of the SDG, as well as examples of actual PH policies, programs and projects that are evidence-based and which health professionals can apply to their work in order to be more sustainable and contribute to the achievement of EPHO3. The workshop has a 'regular workshop' format with 90 minutes total. It is separated into 3 parts, each with a different speaker (15 minutes each, with a regular presentation type format): What is happening? World overview (Teresa Garcia) What can everyone do about it? The science behind creating a habit and sustainable individual choices that contribute to the SDG (Raquel Vareda) What can Public Health do about it? Relevant PH policies, programs and projects that are evidence-based and contribute to better PH and sustainable health systems (Juan Rachadell) Between presentations there will be a 5-minute break for Q&A. In the last 30 minutes, the participants will work in small groups to discuss PH projects in which they're currently/have been involved, and they'll be asked to choose or imagine a project and present a more sustainable way of creating and applying it. All projects will be shared and commented on by every group and by the trainers of the workshop. Key messages: As an individual, you will learn practical actions that you can take in order to contribute to EPHO3 and the SDGs. As a PH professional, you will learn which projects, programs and policies are currently aiming for a more sustainable world.